CARRYING CAPACITY AND REFERENCE OF ECOLOGICAL RESILIENCE OF THE AGUA BLANCA STATE PARK - Romero Juárez, Mariela Conchita; Zequeira Larios, Carolina; Gama Campillo, Lilia María; Martínez Sánchez, José Luis (Kuxulkab’, 2023)
The main pillars that sustain nature tourism are the natural environment and the human factor. Suppose it is intended to obtain a positive result from tourism, especially that based on nature. In that case, it is necessary to consider aspects that allow the sustainable interaction of natural resources, tourists, and host populations. The purpose of this document is to make known the tourist carrying capacity of each of the areas for tourist use that make up the Agua Blanca State Park and how these values allow visualizing areas for improvement in the protected natural area to strengthen the ecological resilience capacity of the site in the face of the potential disturbance of tourism activity in it. It is concluded that the tourist carrying capacity figures provide essential information that allows identifying opportunities to improve and establish management strategies that enhance tourist services and maintain the beauty and resilience of the protected natural area.